2015
DOI: 10.1007/s10346-015-0592-3
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and precipitation-displacement modelling of rainfall-induced deep-seated landslides subject to creep deformation

Abstract: International audienceWe propose an approach to study the hydro-mechanical behaviour and evolution of rainfall-induced deep-seated landslides subjected to creep deformation by combining signal processing and modelling. The method is applied to the Séchilienne landslide in the French Alps, where precipitation and displacement have been monitored for 20 years. Wavelet analysis is first applied on precipitation and recharge as inputs and then on displacement time-series decomposed into trend and detrended signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 63 publications
(117 reference statements)
2
46
0
Order By: Relevance
“…Large rock slope failures are commonly delayed with respect to deglaciation, supporting the hypothesis that they undergo progressive failure in subcritical stress conditions (Brideau et al, ; Chigira, ; Eberhardt et al, ). These are mirrored by a commonly observed time‐dependent “slope creep” (Emery, ), characterized by rather constant, low displacement rates to which seasonal accelerations are often superimposed (Crosta & Agliardi, ; Vallet et al, ). The latter are usually interpreted as evidence of coupling between hydrological triggers and landslide systems (Crosta et al, ; Preisig et al, 2016; Vallet et al, ).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Large rock slope failures are commonly delayed with respect to deglaciation, supporting the hypothesis that they undergo progressive failure in subcritical stress conditions (Brideau et al, ; Chigira, ; Eberhardt et al, ). These are mirrored by a commonly observed time‐dependent “slope creep” (Emery, ), characterized by rather constant, low displacement rates to which seasonal accelerations are often superimposed (Crosta & Agliardi, ; Vallet et al, ). The latter are usually interpreted as evidence of coupling between hydrological triggers and landslide systems (Crosta et al, ; Preisig et al, 2016; Vallet et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…These are mirrored by a commonly observed time‐dependent “slope creep” (Emery, ), characterized by rather constant, low displacement rates to which seasonal accelerations are often superimposed (Crosta & Agliardi, ; Vallet et al, ). The latter are usually interpreted as evidence of coupling between hydrological triggers and landslide systems (Crosta et al, ; Preisig et al, 2016; Vallet et al, ). Although movements progressing to catastrophic collapse may result from rock mass failure without external forcing (i.e., tertiary creep; Rose & Hungr, ; Saito & Uezawa, ; Voight, ; Zavodni & Broadbent, ), hydromechanical coupling has been recognized to play an increasingly important role as rockslides attain mature stages of evolution (Crosta et al, ).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Sun et al [8] simulated the hydraulic-mechanic coupling process of Sanmendong landslide by software product ABAQUS and confirmed that the combined result of reservoir water level fluctuation and rainfall could primarily account for the increase of displacement of this landslide. Vallet et al [9] studied the hydromechanical behavior and evolution of rainfall-induced landslides subjected to creep deformation. The previous researches are mainly based on the steady-state method, by calculating variables of the model under different 2 Geofluids reservoir water levels, so as to approximately simulate the dynamic process of reservoir water level variation.…”
Section: Introductionmentioning
confidence: 99%